KEMAMPUAN BERPIKIR KREATIF SISWA PADA SISTEM PERNAPASAN MELALUI PENERAPAN TEAM GAME TURNAMEN (TGT) BERBANTU MONOPOLI - Nurjamilah, Intan Permatasari; Ukit, Ukit; Muttaqin, Muhammad (Jurnal BIOEDUIN, 2021)
The background of the research is based on the problems related to learning of science that is less emphasizing in the creative thinking abilities of students, so students have difficulty to polish their ability to solve the problems in learning. Teachers must be able to create new innovations in learning that can enhance students' creative thinking abilities. This study aims to determine the effect of the monopoly-assisted TGT learning model in students' creative thinking abilities on respiratory system material. The method which is used is a Quasi-Experiment, with a control group pretest-posttest design and sampling techniques with simple random sampling. The research sample is taken from class VIII-C as a control class and VIII-D as an experimental class, each of which has 30 students using the creative thinking skills test instrument, observation sheet, and student questionnaire responses. Improving students' creative thinking skills using the monopoly-assisted TGT model on respiratory system material obtained an N-Gain value 0,61 in the medium category. The effect of the monopoly-assisted TGT model on students' creative thinking abilities with the t-test shows that tcount (8,07)> ttable (2,00), means that there is a significant influence between the experimental class and the class control. The conclusion of the study is that the use of the monopoly-assisted TGT learning model in learning has an effect on increasing students' creative thinking abilities on the material of the human respiratory system.